Precision genomic profiling in Gaucher disease: insights from atypical presentations - Saith, Armaan; Ain, Noor Ul; Ruan, Jiapeng; Kasaiyan, Maniya; Jain, Dhanpat; Israel, Gary; Mehta, Sameet; Bamford, Nigel S.; Nair, Shiny; Mistry, Pramod K. (Frontiers in Genetics, 2025)
BackgroundGaucher disease (GD) is characterized by significant phenotypic heterogeneity, even among patients with identical GBA1 genotypes, suggesting the role of genetic and/or epigenetic modifiers. The enzymatic defect and pathological accumulation of glucosylceramide (GlcCer) lead to chronic metabolic inflammation, providing ample opportunities for interaction with other biological pathways to influence disease expression. Herein, we developed a model of precision medicine in this prototype single-gene disorder.MethodsThis study leveraged a well-characterized, longitudinally followed cohort of GD patients from a major tertiary care center, integrating whole-exome sequencing (WES) with detailed clinical information. We applied a precision medicine framework centered on four components—clinical reasoning, deep phenotyping, genomic integration, and individualized therapy—to a subset of patients (n = 17) who presented with complex phenotypes deviating from the classical GD presentation and/or were a priori suspected of harboring a second genetic disorder.ResultsOf 275 patients, 17 (6.2%) presented with atypical phenotypes not fully explained by GD. WES revealed additional genetic diagnoses, including hereditary hemochromatosis-associated variants (n = 5), familial Mediterranean fever (n = 4), homozygous MSH6 mutation-associated hereditary cancer predisposition (n = 2), and autosomal dominant polycystic kidney disease (ADPKD) (n = 2).ConclusionThe presence of concurrent genetic disorders in a subset of GD patients has the potential to modify clinical presentation, impact disease trajectory, and introduce additional complexities in clinical management. This study contributes to advancing precision medicine strategies that aim to optimize patient outcomes. Future research into genetic and epigenetic modifiers of GD will further refine this framework and enhance individualized therapeutic approaches.